Characterization of a Southern Ocean deep chlorophyll maximum: Response of phytoplankton to light, iron, and manganese enrichment - Pauline Latour; Sam Eggins; Pier van derMerwe; Lennart T. Bach; Philip W. Boyd; Michael J. Ellwood; Andrew R. Bowie; Kathrin Wuttig; Robert F. Strzepek (Limnology and Oceanography Letters, 2024)
Abstract Southern Ocean phytoplankton growth is limited by low iron (Fe) supply and irradiance, impacting the strength of the biological carbon pump. Unfavorable upper ocean conditions, such as low nutrient concentrations, can lead to the formation of deep chlorophyll or biomass maxima (DCM/DBM). While common in the Southern Ocean, these features remain understudied due to their subsurface location. To increase our understanding of their occurrence, we studied the responses of phytoplankton communities from a Southern Ocean DCM to increasing light, Fe, and manganese (Mn) levels. The DCM communities were light‐ and Fe‐limited, but light limitation did not increase phytoplankton Fe requirements. The greatest physiological responses were observed under combined Fe/light additions, which stimulated macronutrient drawdown, biomass production and the growth of large diatoms. Combined Mn/light additions induced subtle changes in Fe uptake rates and community composition, suggesting species‐specific Mn requirements. These results provide valuable information on Southern Ocean DCM phytoplankton physiology.